THE ROLE OF ACCOUNTING RECORDS IN HALAL MICRO SMALL AND MEDIUM ENTERPRISES (MSMEs) ( Case Study of Halal MSMEs in Medan Denai District ) - Hayati, Isra; Olivia, Hastuti; Afandi, Ahmad; Amalia, Alfi (Proceeding International Seminar of Islamic Studies, 2024)
Research purposes This For know role recording accounting for Halal Micro , Small and Medium Enterprises (MSMEs) at Halal MSMEs, Medan Denai District . Approach research used _ use approach qualitative . Deep data collection techniques study This use results observation and interviews . Respondent in study This consists from Owner MSME businesses Halal Medan Denai District which consists of from types of Culinary MSMEs. Research result show that recording accounting for Halal MSMEs has very important role . Role recording accountancy for MSMEs have role as monitoring finance , Decision making , compliance tax , access financing , monitoring debts and receivables , planning finance , monitoring efficiency operations and internal control .